Pollyanna - Porter, Eleanor H. (Not mentioned: Wonder House, 2021)
Orphaned and penniless, little Pollyanna doesn$1 (Bt seem to have much to look forward to in life. When she moves in with the strict and cold Aunt Polly, things take a turn for the worse. Thankfully, Pollyanna has a special power$1 (Bthe ability to be glad about whatever comes her way. Will Pollyanna be able to keep up her sunny disposition? Or will she succumb to the misfortunes of her life? Read the sweet tale of Pollyanna to witness how she finally finds something to be glad for, and finds family in the most unlikely places.s